The XVth Banff Conference on Allograft Pathology the Banff Workshop Heart Report: Improving the diagnostic yield from endomyocardial biopsies and Quilty effect revisited. Issue 12 (28th June 2020) - Duong Van Huyen, Jean‐Paul; Fedrigo, Marny; Fishbein, Gregory A.; Leone, Ornella; Neil, Desley; Marboe, Charles; Peyster, Eliot; von der Thüsen, Jan; Loupy, Alexandre; Mengel, Michael; Revelo, Monica P.; Adam, Benjamin; et al.
Abstract : The XVth Banff Conference on Allograft Pathology meeting was held on September 23‐27, 2019, in Pittsburgh, Pennsylvania, USA. During this meeting, two main topics in cardiac transplant pathology were addressed: (a) Improvement of endomyocardial biopsy (EMB) accuracy for the diagnosis of rejection and other significant injury patterns, and (b) the orphaned lesion known as Quilty effect or nodular endocardial infiltrates. Molecular technologies have evolved in recent years, deciphering pathophysiology of cardiac rejection. Diagnostically, it is time to integrate the histopathology of EMBs and molecular data. The goal is to incorporate molecular pathology, performed on the same paraffin block as a companion test for histopathology, to yield more accurate and objective EMB interpretation. Application of digital image analysis from hematoxylin and eosin (H&E) stain to multiplex labeling is another means of extracting additional information from EMBs. New concepts have emerged exploring the multifaceted significance of myocardial injury, minimal rejection patterns supported by molecular profiles, and lesions of arteriolitis/vasculitis in the setting of T cell–mediated rejection (TCMR) and antibody‐mediated rejection (AMR). The orphaned lesion known as Quilty effect or nodular endocardial infiltrates. A state‐of‐the‐art session with historical aspects and current dilemmas was reviewed, and possible pathogenesis proposed, based on advances in immunology to explain conflicting data. The Quilty effect will be the subject of a multicenter project to explore whether it functions as a tertiary lymphoid organ. Abstract : The authors summarize proceedings of the Heart Transplant group during the XVth Banff Conference on Allograft Pathology in 2019.